Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Tan, Yi Mei; Dalby, Oliver; Kendrick, Gary A.; Statton, John; Sinclair, Elizabeth A.; Fraser, Matthew W.; Macreadie, Peter I.; Gillies, Chris L.; Coleman, Rhys A.; Waycott, Michelle; van Dijk, Kor-jent; Vergés, Adriana; et al. (Frontiers in Marine Science, 2020)
Seagrasses are important marine ecosystems situated throughout the world’s coastlines. They are facing declines around the world due to global and local threats such as rising ocean temperatures, coastal development and pollution from sewage outfalls and agriculture. Efforts have been made to reduce seagrass loss through reducing local and regional stressors, and through active restoration. Seagrass restoration is rapidly maturing but improved restoration practices are needed to enhance the success of future programs. Major gaps in knowledge remain, especially our understanding of how to restore tropical species in Australia. Prior research efforts have provided valuable insights into factors influencing the outcomes of restoration and there are now several examples of successful large-scale restoration programs. A variety of tools and techniques have recently been developed that will improve the efficiency, cost effectiveness, and scalability of restoration programs. This review describes emerging techniques for restoration, key considerations for future programs, and highlights the benefits of increased collaboration, Traditional Owner (First Nation) and stakeholder engagement. Combined, these lessons and emerging approaches show that seagrass restoration is possible and efforts should be directed at upscaling seagrass restoration into the future. This is critical for the future conservation of this important ecosystem and the ecological and coastal communities they support.